Advances in melt electrowriting for cardiovascular applications - Mueller, Kilian Maria Arthur; Mansi, Salma; De-Juan-Pardo, Elena M.; Mela, Petra (Frontiers in Bioengineering and Biotechnology, 2024)
Melt Electrowriting (MEW) is an electric field-assisted additive biofabrication technique that has brought significant advancements to bioinspired scaffold design for soft tissue engineering and beyond. Owing to its targeted microfiber placement, MEW has become a powerful platform technology for the fabrication of in vitro disease models up to functional biohybrid constructs that are investigated in vivo to reach clinical translation soon. This work provides a concise overview of this rapidly evolving field by highlighting key-contributions of MEW to cardiovascular tissue engineering. Specifically, we i) pinpoint the methods to introduce microvascular networks in thick 3D constructs benefitting from (sacrificial) MEW microfibers, ii) report MEW-based concepts for small-diameter vascular grafts and stents; iii) showcase how contracting cardiac tissues can profit from the tunable structure-property relationship of MEW scaffolds, and iv) address how complete regenerative heart valves can be built on complex fiber scaffold architectures that recapitulate Jshaped tensile properties and heterogeneity of the tissue. Lastly, we touch on novel biomaterial advancements and discuss technological challenges of MEW to unlock the full potential of this transformative technology.